Hubungan Komunikasi Terapeutik Dengan Kepuasan Pasien Rawat Inap Puskesmas Tapen Kabupaten Bondowoso - Hidayatullah, Mohammad Syarif (Jurnal Keperawatan Profesional, 2020)
Therapeutic communication is very important for the image of the nursing profession and the image of the hospital. Communication that occurs at the Tapen Puskesmas is still ineffective, so misunderstandings between nurses and patients often occur. The purpose of this research is to find out. The relationship between therapeutic communication with inpatient patient satisfaction at Tapen Health Center in Bondowoso Regency and to find out how big is the relationship between Therapeutic Communication and Patient Satisfaction in the Inpatient Room at Tapen Health Center in Bondowoso Regency. This research method is quantitative. This research was conducted in May 2019 with a sample of 30 inpatients. The sampling technique uses total sampling where the p-value has a significant relationship and Ha is received between therapeutic communication and patient satisfaction. The results of this study indicate that the relationship between Therapeutic Communication Nurse with Inpatient Satisfaction in Tapen Health Center, Bondowoso Regency, a significant relationship between therapeutic communication with inpatient satisfaction. The level of therapeutic communication relationship with patient satisfaction.